2014
DOI: 10.5603/fhc.2014.0013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-thyroxine treatment on peripheral blood dendritic cell subpopulations in patients with Hashimoto’s thyroiditis

Abstract: Recent reports suggested dendritic cells (DCs) to be important players in the pathogenesis of autoimmune thyroid processes in humans. However, there are virtually no data addressing the influence of thyroid autoaggression-associated disturbances of thyrometabolic conditions on DCs biology. The aim of the study was to evaluate the influence of L-thyroxine supplementation on conventional and plasmacytoid peripheral blood DCs subtypes in patients with hypothyroidism due to Hashimoto's thyroiditis (HT). Eighteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Dedecjus et al (103) reported that the thyrometabolic state influenced the major human peripheral blood DCs, pDCs, and cDCs, with T4 substitution to thyroid cancer patients after surgery increasing the frequency of these cells and the expression of CD86 and HLA-DR (activation markers). In hypothyroid patients with Hashimoto's Thyroiditis, T4 supplementation exerted changes of peripheral blood DC subpopulations, with increased expression of costimulatory molecules (104). Although TRs in human DC populations have not yet been found, increased expression of CD86 by T3 addition to cell cultures of human peripheral blood pDCs was reported (103).…”
Section: Introductionmentioning
confidence: 99%
“…Dedecjus et al (103) reported that the thyrometabolic state influenced the major human peripheral blood DCs, pDCs, and cDCs, with T4 substitution to thyroid cancer patients after surgery increasing the frequency of these cells and the expression of CD86 and HLA-DR (activation markers). In hypothyroid patients with Hashimoto's Thyroiditis, T4 supplementation exerted changes of peripheral blood DC subpopulations, with increased expression of costimulatory molecules (104). Although TRs in human DC populations have not yet been found, increased expression of CD86 by T3 addition to cell cultures of human peripheral blood pDCs was reported (103).…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of L-T4 supplementation was different in patients with Hashimoto's disease. In this group of patients, the level of pDCs in the PBMC fraction decreased during the L-T4 treatment, while the percentage of cDCs remained unchanged (36).…”
Section: Discussionmentioning
confidence: 66%
“…On the other hand, the results of different study have suggested the presence of the direct effect of L-thyroxine therapy on the percentages of selected populations of dendritic cells (DCs), with a significant reduction among their plasmacytoid subtype in peripheral blood and no changes concerning the total number of conventional DCs. However, the cluster of conventional DCs expressing CD86 and CD91 was shown to have a greater percentage [51]. The normalization of serum TSH level doses does not have to optimize serum T3; it concerns particularly individuals with a decreased effectiveness of conversion between T4 and T3.…”
Section: Possible Therapeutic Trends In Chronic Thyroiditis-what Do W...mentioning
confidence: 98%